An ARIMA Modeling of the Exchange Rate of the Nigerian Naira to the US Dollar with Covid-19 Pandemic Event in Focus - ODUNTAN, EMMANUEL (Journal of Statistical Modeling and Analytics (JOSMA), 2024)
We modelled the average monthly exchange rate between the Nigerian Naira and the USDollar using univariate time series analysis. With a data set covering January 2002 to June 2022, we divided the data set into three distinct periods, vis-à-vis; the Pre COVID-19 pandemic period, the COVID-19 period, and the Combined period (combination of both pre-COVID-19 and COVID-19 periods). This was done with a view to examining the effect of COVID-19 pandemic on the generation mechanism of the Naira/USDollar exchange rate. The Naira/USDollar exchange rate data was found to be non-stationary and was appropriately differenced to attain stationarity. Subsequently, we fitted ARIMA models for each of the three scenarios using Box Jenkins methodology. Finally, the estimated models were used for forecasting. While the estimated models for both the Pre COVID-19 and the Combined periods yielded forecast values that suggest future depreciation of the Naira against the USDollar, that of the COVID-19 period yielded forecast values that suggest future appreciation of the Naira against the USDollar.